(untitled) (AmeriQuests, 2021)
The aim of this paper is to present how the “Street Vendors Popular Syndicate of Barcelona”, a bottom-up organisation composed mainly by undocumented Senegalese migrants, develops political narratives and repertoires of actions through rap music and clothing design. Despite the precarious situations and multifaceted forms of ‘illegality’ that the sindicato members face, this unconventional political organisation is still characterized by high and complex levels of visibility, support and creativity. Drawing on ethnographic fieldwork, this article analyses two artistic projects developed by the collective: the rap song “This is the Syndicate” and the clothing brand “Top Manta”. In doing so, the research shows that the sindicato has been effective in empowering through arts and redefining the multiple stigmas of ‘illegality’ targeting the organisation. In a nutshell, this paper provides a better understanding of undocumented migrants’ political solidarity and promising artistic creativity despite precarity and multifaceted discrimination in Southern European countries.